The influence of Parent’s Socio-Economic Status, Family Financial Governance, Financial Learning in Higher Education on Financial Literacy, Lifestyle and Human Capital Investment of Economics and Business Students in Batam City, Indonesia - Wibow, Agung Edy; Ratnawati, Tri; Sardjono, Sigit (Archives of Business Research, 2019)
The capacity of human capital, today has become a strategic issue in achieving prosperity of nations. Some of nation which has a high or good level at human capital index will be have a significantly impact on achieving prosperity on a nation’s society, including Indonesia and specially Batam city which has been becoming part of young province in Indonesia and close to Singapore as a central of economics world. Batam must be ready to increase and prepare all of resources which it can be increasing personal prosperity and increasing the goodness of life in the future by using investing in human capital. This research has mainly goals to demonstrate and analyze the influence of parent’s socio-economic status, family financial governance, financial learning in higher education, on financial literacy, lifestyle and human capital investment. The population in this research was 1.233 respondent of economics and business students in Batam, Riau Province in Indonesia, and the sample numbered 302 students. Analyzing data in this research was using SEM (Structural Equation Modeling) with AMOS ver. 20. The result of discussion can be concluded that parent’s socio-economic did not effects significantly to financial literacy, parent’s socio-economic effects significantly to lifestyle, parent’s socio-economic effects significantly to human capital investment. Family financial governance effects significantly to financial literacy, Family financial governance did not effects significantly to lifestyle, Family financial governance effects significantly to human capital investment. Financial learning in higher education effects significantly to financial literacy, financial learning in higher education did not effects significantly to lifestyle, financial learning in higher education effects significantly to human capital investment. Financial literacy effects significantly to lifestyle, financial literacy effects significantly to human capital investment. Lifestyle effects significantly to human capital investment. Keywords: parent’s socio-economic status, family financial governance, financial learning in higher education, financial literacy, lifestyle, and human capital investment.